KAJIAN PENGEMBANGAN KAWASAN STRATEGIS SEKTOR PERDAGANGAN DAN JASA KOTA BANDA ACEH (STUDI KASUS KECAMATAN LUENG BATA) - Ridhia Maisarina; Mirza Irwansyah; Izziah Izziah (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2017)
Abstract: As the capital city of Aceh province, Banda Aceh was selected as one of the strategic areas based on its potential, accessibilty and sectoral distribution activities for the city itself and for the sorrounding areas (hinterlands). Qanun (Local regulation) of spatial planning of Banda Aceh city number 04 in 2009 stated that one of Banda Aceh city’s strategic planning area is at Lueng Bata district and sorrounds. Lueng Bata district condition currently to growth as roads development and so that the population continues to growth 0.40 % from last year (yr. 2015), with a population density of 4,965 inhabitants per km2. If Lueng Bata district was developed as a strategic area of the city, it is necesessary to study in spatial and region development in term of demographic aspects, economic aspects and aspects of public services. The scope of the research is the study on the infrastructure of Banda Aceh city, which are urban system or central urban services, and infrastructure in particular regions transport network. The research methods used are the combination of qualitative and quantitative descriptive with case study approach. Data collected by doing the observation, interviews, and questionnaires. Variabels used are numbers of pupulation, number of public facilities and the accessibilty to surrounds area (hinterland). It’s analized by urban order, gravity (the attractiveness of the region), and AHP. The results study showed that strategic area of Lueng Bata district can be developed into mixed trade and sevices area, but need to be equipped with the public service facilities and infrastructure like traditional and modern markets, and it has the opportunity to undertake regional cooperation in trade and services sector with Aceh Besar district as hinterland for economic development in Aceh Province.Abstrak: Banda Aceh sebagai ibukota Provinsi Aceh merupakan salah satu kawasan strategis berdasarkan potensi, aksesibilitas dan sebaran kegiatan sektoral untuk wilayah kota dan sekitarnya (hinterland). Qanun Rencana Tata Ruang Wilayah (RTRW) Nomor 4 Tahun 2009 menetapkan salah satu pengembangan kawasan strategis kota berada di Kecamatan Lueng Bata dan sekitarnya. Kondisi Kecamatan Lueng Bata saat ini terus berkembang mengikuti pengembangan jalan (ribbons development) dan pertambahan penduduk yang terus meningkat 0,40 % (tahun 2015), dengan kepadatan penduduk Kecamatan Lueng Bata sebesar 4.965 jiwa per km2. Apabila Kecamatan Lueng Bata dikembangkan sebagai kawasan strategis kota, maka diperlukan kajian dalam penataan dan pembangunan wilayah yang ditinjau dari aspek kependudukan, aspek ekonomi dan aspek pelayanan publiknya. Lingkup penelitian adalah kajian pada infrastruktur Kota Banda Aceh yaitu sistem perkotaan atau pusat pelayanan perkotaan, dan sarana-prasarana wilayah khususnya jaringan transportasi. Penelitian menggunakan metode gabungan yaitu kualitatif, kuantitatif dan deskriptif dengan pendekatan studi kasus. Pengumpulan data dilakukan dengan cara observasi, wawancara, dan kuesioner. Variabel yang digunakan adalah jumlah penduduk, jumlah fasilitas dan tingkat aksesibilitasnya dengan kawasan sekitar. Analisa data yang digunakan adalah orde perkotaan, gravitasi dan AHP. Hasil penelitian menunjukkan bahwa kawasan strategis Kecamatan Lueng Bata dapat dikembangkan menjadi kawasan perdagangan dan jasa campuran namun perlu dilengkapi dengan sarana dan prasarana pelayanan publik yaitu pasar tradisional dan pasar modern, serta berpeluang untuk dilakukannya kerjasama regional sektor perdagangan dan jasa dengan wilayah Kabupaten Aceh besar sebagai hinterland untuk kemajuan ekonomi di Provinsi Aceh.